Streptokinase in acute myocardial infarction: a controlled multicentre study in the United Kingdom. Issue 6044 (6th November 1976) - Aber, C P; Bass, N M; Berry, C L; Carson, P H; Dobbs, R J; Fox, K M; Hamblin, J J; Haydu, S P; Howitt, G; MacIver, J E; Portal, R W; Raftery, E B; et al.
Abstract : In a multicentre trial of streptokinase in acute myocardial infarction 302 patients received an intravenous infusion of 2 500 000 IU of streptokinase over 24 hours, while 293 patients served as controls. Neither group received anticoagulants unless indicated by thromboembolic complications. No significant difference in mortality was evident during inpatient treatment nor at six-week or six-month follow-up. The inpatient death rate was 12-6% in the streptokinase group and 13-7% among controls. There was no significant difference in the peak levels or pattern of enzyme increase. The incidence of cardiac failure and reinfarction was similar in the two groups, but major arrhythmias were less common in those on streptokinase (P less than 0-05). In the streptokinase group there were 36 minor and six more serious haemorrhagic complications. Gastrointestinal haemorrhage may have contributed to the death of one patient in each group. There were 18 thromboembolic complications in the streptokinase group and 38 among the controls. Pathological examination of the hearts of 25 patients who had taken streptokinase and 24 controls showed no striking differences between the groups, but haemorrhagic infarcts were found in three patients who had received streptokinase. An infusion of streptokinase within 24 hours of the onset of acute myocardial infarction does not significantly affect the mortality or course of the illness up to six months.